Vector-borne diseases on Borneo island: a scoping review - Song‑Quan Ong; Ag Shazmeer Ag Safree; Nur Badriah Asmail Ismai (ResearchGate, 2024)
Background Borneo, the third largest island in the world, is facing a signifcant burden of emerging and re-emerging vector-borne diseases due to rapid changes in primary tropical rainforests and urban landscapes. These vectorborne diseases include the endemic epidemic cycles that occur in the more populated and urbanized areas, as well as the possible transmission through enzootic and sylvatic transmission cycles that occur mainly in the overlapping landscapes or among the indigenous population in the forest. The island will be changed signifcantly in the future due to the increase in human activities, especially mega events such as the relocation of the Indonesian capital to Nusantara in East Kalimantan Borneo, increasing urbanization, agriculture, hydropower projects, ecotourism activi‑ ties in Sabah, North Borneo, and Sarawak, Central and South Borneo. Therefore, an overview of the current situation of vector-borne diseases is crucial for the next possible epidemic preparedness. Methods This study conducted the PRISMA-ScR scoping review and formulated a set of research questions to iden‑ tify current trends in vector-borne diseases in Borneo. These questions aim to identify which diseases have been studied, what geographical areas have been covered by the research, how the One Health approach—encompassing human, animal and environmental factors—is integrated, and what gaps and challenges exist in addressing these diseases Results A total of 2241 references were screened for eligibility and 117 articles were selected for review. The majority of the materials focused on mosquitoes and malaria, and the One Health elements focused mainly on humans. Conclusions This review has identifed the most and least studied vector-borne diseases and highlighted some of the gaps in knowledge and research on vector-borne diseases on the island of Borneo. Future studies should par‑ ticularly focus on other neglected diseases such as Zika, chikungunya, Japanese encephalitis, flariasis and tick-borne diseases. In addition, advanced surveillance systems will be developed to improve early detection and response specifcally for remote regions where vector-borne diseases are endemic or emerging.